Placenta accreta spectrum ultrasound stage and fetal growth. Issue 3 (28th August 2022) - Bartels, Helena C.; Walsh, Jennifer M.; O'Connor, Clare; McParland, Peter; Carroll, Stephen; Higgins, Shane; Mulligan, Karen M.; Downey, Paul; Brophy, David; Colleran, Gabrielle; Thompson, Claire; Walsh, Tom; et al.
Abstract: Objective: to evaluate fetal growth in pregnancies complicated by placenta accreta spectrum (PAS) and to compare fetal growth between cases stratified by ultrasound stage of PAS. Methods: This was a prospective multicenter cohort study of women diagnosed with PAS between January 2018 and December 2021. We grouped participants into cases by ultrasound stage (PAS stage 1–3) and controls (PAS0). Fetal growth centiles at three timepoints with median gestational ages of 21 ± 1 weeks (interquartile range [IQR], 20 ± 1–22 ± 0 weeks), 28 ± 0 weeks (IQR, 27 ± 0–28 ± 5 weeks), and 33 ± 0 weeks (IQR, 32 ± 1–34 ± 0 weeks) and birth weight centiles were compared between cases and controls and between those with PAS stratified by ultrasound stage. Results: A total of 53 women met inclusion criteria, with a mean age of 37 years (standard deviation, ±4.0 years) and body mass index of 27 kg/m 2 (standard deviation, ±5.8 kg/m 2 ). Median (IQR) fetal weight centiles were around the 50th centile at each timepoint, with no difference between groups. The incidence of small for gestational age (birth weight ≤ 10th percentile) and large for gestational age (birth weight ≥ 90th percentile) was 11.3% ( n = 6) and 15.1% ( n = 8), respectively, with no differences by ultrasound stage. The median birth weight centile was 64 (IQR, 26–85), with no differences between cases and controls or by ultrasound stage. Conclusions: In our cohort, a diagnosis of PAS was not associated with fetal growth restriction. Synopsis: Placenta accreta spectrum does not seem to result in placental insufficiency and fetal growth abnormalities, with normal growth seen across all stages of ultrasound severity in our cohort.